2005
DOI: 10.1029/2005jc002927
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution numerical simulations of resuspending gravity currents: Conditions for self‐sustainment

Abstract: [1] We introduce a computational model for high-resolution simulations of particle-laden gravity currents. The features of the computational model are described in detail, and validation data are discussed. Physical results are presented that focus on the influence of particle entrainment from the underlying bed. As turbulent motions detach particles from the bottom surface, resuspended particles entrained over the entire length of the current are transferred to the current's head, causing it to become denser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 50 publications
5
112
0
1
Order By: Relevance
“…The lateral development of density-driven flow in a subaqueous channel is studied using a 3D numerical model, in the work of Imran et al [20]. The conditions under which turbidity currents may become selfsustaining through particle entrainment are investigated in the work of Blanchette et al [21], using 2D Direct Numerical Simulations of resuspending gravity currents. A numerical model of turbidity currents with a deforming bottom boundary, that predicts the vertical structure of the flow velocity and concentration as well as the change in the bed level, due to erosion and deposition of suspended sediment, is developed in the work of Huang et al [22].…”
Section: Introductionmentioning
confidence: 99%
“…The lateral development of density-driven flow in a subaqueous channel is studied using a 3D numerical model, in the work of Imran et al [20]. The conditions under which turbidity currents may become selfsustaining through particle entrainment are investigated in the work of Blanchette et al [21], using 2D Direct Numerical Simulations of resuspending gravity currents. A numerical model of turbidity currents with a deforming bottom boundary, that predicts the vertical structure of the flow velocity and concentration as well as the change in the bed level, due to erosion and deposition of suspended sediment, is developed in the work of Huang et al [22].…”
Section: Introductionmentioning
confidence: 99%
“…There has been some success in modelling these flows using DNS in two dimensions which makes the problem more computationally tractable (Blanchette et al, 2005;Ooi et al, 2007). However, Espath et al (2014) showed that the only important diagnostic that can be accurately predicted using a two-dimensional DNS model is the sedimentation rate.…”
Section: S D Parkinson Et Al: Direct Numerical Simulations Of Partmentioning
confidence: 99%
“…This model is used to describe the erosion of sediment from a cohesive bed or from a bed of fine cohesionless material where some critical shear stress must be exceeded in order to entrain particles from the bed into the water column [2,9,10,[15][16][17].…”
Section: Model Developmentmentioning
confidence: 99%